BASIC INDICATORS OF ILLEGAL HUNTING - M. G. Abdulmutalibov (Юг России: экология, развитие)
Aim. The article deals with some of the features of objective side of illegal hunting and problems of their applying under the current legislation. We give the most accurate interpretation of the direct objects of illegal hunting which are the following: public relations to ensure the safety, rational use, rehabilitation and reproduction of freeliving wild animals and birds and the preservation of the number of animals required.Methodology. We use methods of description and interpretation.Results. We identified some features of illegal hunting: a) without authorization; b) despite the specific prohibition; c) by person not having the right to hunt or having a license without proper grounds; d) hunting outside of the designated areas; e) hunting in closed seasons; e) prohibited hunting tools and methods.Main conclusions. From legislation, permissions for hunting are the following: hunting permits, hunting license; nominal one-time license for the hunting of animals and birds, the contract on delivery of meat and furs, etc. It is found that in Russia the hunting farms are in a poor state because of the lack of well-established legal and regulatory framework; the lack of effective management and the negative impact of the reforms as a whole; when normative legal acts are being developed, the centuries-old experience of foreign countries and the opinion of scientists and hunters are not taken into account.